Unfamiliar Races in Untimely Places: Anti‐Essentialism and the Science Fiction Television Series The Expanse. (Journal of Popular Culture (John Wiley & Sons, Inc.), 2022)
The article analyzes the science fiction television (TV) series "The Expanse," adapted from the novel of the same name by James S. A. Corey. Topics discussed include comparison between this show and other science fiction TV programs, brief details about its setting, plot, and characters, and the way the program addressed themes such as racial classifications, power, and privilege.